Epoxy glue for semiconductor cutting splicing rod and preparation method of epoxy glue
Through the combination of POSS-epoxy and phenolic epoxy, combined with modified amine curing agent and spherical filler, the insufficient performance of existing stick glues under temperature changes and high temperatures is solved, and high glass transition temperature and temperature resistance are achieved Performance epoxy adhesive improves the quality and safety of semiconductor cutting.
Patent Information
- Application Number
- CN202411879929.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing semiconductor stick glue lacks glass transition temperature, hardness and temperature resistance during the cutting process, resulting in a decrease in performance under temperature changes and high temperatures, affecting cutting quality and safety.
Using POSS-epoxy cage polysilsesquioxane and phenolic epoxy as main components, combined with a modified amine curing agent and a spherical filler with a low linear expansion coefficient, the combination of components A and components B is formed with Epoxy glue with high glass transition temperature and temperature resistance.
The hardness and temperature resistance of epoxy glue are improved, so that it can remain stable during the cutting process, reduce the wire bow, improve the cutting yield, and reduce the water absorption and brittleness of the colloid.
Smart Images

Figure SMS_6 
Figure SMS_7 
Figure SMS_8
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy adhesives, and in particular to an epoxy adhesive for semiconductor cutting and splicing bars and a preparation method thereof. Background Art
[0002] In the field of semiconductor silicon carbide / silicon wafer cutting, since the semiconductor crystal pulling growth process is relatively long and it is difficult for silicon carbide semiconductors to grow into larger single rods, in order to ensure the batch and uniformity of each cutting, silicon carbide semiconductor rods of different lengths are usually spliced together according to the crystal orientation and then cut at the same time.
[0003] The existing glue for splicing bars on the market are mainly used for photovoltaic-grade monocrystalline silicon and polycrystalline silicon splicing bar cutting. They mainly include epoxy-modified amine glue, unsaturated bisphenol A acrylate glue, and oxide (copper, iron, yttrium, lanthanum) inorganic glue, with epoxy-modified amine glue being the most common. However, epoxy-modified amine glue, such as epoxy splicing bar glue, has great limitations. Compared with silicon wafers, the third-generation semiconductor silicon carbide has a higher hardness (9.2 Mohs hardness) and is usually more brittle than semiconductor silicon wafers. Although traditional photovoltaic-grade epoxy splicing bar glue is brittle at room temperature, it has a low glass transition temperature and poor temperature resistance. Especially during the cutting process, as the temperature and water absorption rate change, the strength and hardness will decrease rapidly. During the bonding and curing process, due to oxygen inhibition, unsaturated bisphenol A acrylate glue reacts with oxygen at the bonding interface, making it difficult to cure the glue and becoming very sticky, resulting in the diamond wire adhering to the glue and reducing the cutting force. In addition, the glue has a strong odor and huge heat release during use, posing a safety hazard. Oxide inorganic glue sticks usually need to be heated and cured, which is quite different from the on-site construction process, and the residual metal ions are difficult to remove, affecting the quality of the semiconductor.
[0004] There have been in-depth studies and explorations in the field of semiconductor silicon rod splicing glue in China. For example, CN118064089A discloses improving the cutting performance of splicing glue by improving the hardness and brittleness of the adhesive at room temperature. However, the glass transition temperature of the common thiol curing agent (DMP-3-800LC) is only 35°C, and the glass transition temperature of the modified amine is only 65°C, which makes it difficult to ensure the deformation caused by the temperature change of the colloid at the moment of cutting. CN115651580B discloses improving the hardness of the glue by adding monomer metal silicon powder, and increasing the density of the glue by adding a large amount of fillers, but the temperature resistance of the common thiol curing agent is still difficult to meet the high temperature of the cutting process, and the amount of fillers in the glue is increased to 81%, which makes it difficult to achieve the fluidity of the glue at room temperature, which is bound to increase the cavitation rate of the glue, resulting in a significant increase in the wire breakage rate during the cutting process. CN117247756B discloses that the temperature resistance is improved by adding phenalkamine and a tetrafunctional mercaptan curing agent. However, due to the limitation of the glass transition temperature of the phenalkamine curing agent, the temperature resistance of the glue stick still cannot meet the hardness requirement at the cutting temperature. Summary of the invention
[0005] The technical problem to be solved by the present invention is to improve the glass transition temperature, hardness and temperature resistance of semiconductor stick glue based on the deficiencies in the prior art.
[0006] In order to solve the above problems, the present invention proposes the following technical solutions: In a first aspect, the present invention provides an epoxy adhesive for semiconductor cutting and splicing rods, comprising component A and component B; The component A comprises the following ingredients in parts by weight: POSS-epoxy caged polysilsesquioxane 17-25 parts by weight; 8-15 parts by weight of phenolic epoxy; 58-72 parts by weight of the first filler; 2-5 parts by weight of the first auxiliary agent; The B component includes the following ingredients in parts by weight: POSS-mercapto caged polysilsesquioxane 17-23 parts by weight; 5-10 parts by weight of modified amine curing agent; 3-5 parts by weight of accelerator; 60-70 parts by weight of the second filler; The second auxiliary agent is 2-3 parts by weight.
[0007] A further technical solution is that the POSS-epoxy caged polysilsesquioxane includes at least one of octa-glycidyl ether POSS-glycidyl ether oxygen propyl caged polysilsesquioxane, alicyclic epoxy POSS-octa-epoxy cyclohexylethyl caged polysilsesquioxane, and glycidyl ether oxygen propyl cyclotetrasiloxane.
[0008] A further technical solution is that the POSS-epoxy caged polysilsesquioxane is octa-glycidyl ether POSS-glycidyl ether oxypropyl caged polysilsesquioxane.
[0009] A further technical solution is that the phenolic epoxy includes at least one of EPICLON HP-4710 (super high heat-resistant epoxy resin), a phenolic epoxy with a DCPD structure (diethylcyclopentadiene phenolic epoxy), and NPPN-638 phenolic epoxy.
[0010] A further technical solution is that the general formula of the POSS-mercapto cage-like polysilsesquioxane is (RSiO3 / 2)n, R is mercaptopropionate, and n=8.
[0011] A further technical solution is that the modified amine curing agent is obtained by condensation reaction of 3,3-dimethyl-4,4-diaminodicyclohexylmethane and thiourea.
[0012] A further technical solution is that the first filler and the second filler are independently selected from at least one of spherical silica, spherical alumina, and spherical silicon carbide with low linear expansion coefficient. It can be understood that spherical silica, spherical alumina, and spherical silicon carbide are all spherical fillers with low linear expansion coefficients, which help to reduce shrinkage after curing and ensure the firmness of the bonding interface.
[0013] A further technical solution is that the spherical silicon dioxide includes spherical silicon dioxide with a particle size of 3-8 μm, spherical silicon dioxide with a particle size of 0.11-1.5 μm, and spherical silicon dioxide with a particle size of 0.01-0.10 μm, and the usage ratio of the three particle sizes is 9-11:1-3:2-0.5; The spherical alumina includes spherical alumina with a particle size of 1-5 μm, spherical alumina with a particle size of 0.2-0.8 μm, and spherical alumina with a particle size of 0.01-0.10 μm, and the usage ratio of the three particle sizes is 7-9:1-3:2-0.5; The spherical silicon carbide includes spherical silicon carbide with a particle size of 5-10 μm, spherical silicon carbide with a particle size of 0.8-3 μm and spherical silicon carbide with a particle size of 0.01-0.10 μm, and the usage ratio of the three particle sizes is 6-8:1-3:2-0.5.
[0014] A further technical solution is that in the first filler and the second filler, the usage ratio of low linear expansion coefficient spherical silica, spherical alumina and spherical silicon carbide is 1-3:2-4:4-6.
[0015] A further technical solution is that the accelerator includes at least one of Versamine EH-50, ACC 2950 (N,N-dimethyl-4-amino-2-azabutyl) phenol), and HI-54K.
[0016] A further technical solution is that the first auxiliary agent and the second auxiliary agent independently include at least one of a defoaming agent, a leveling agent and a dispersant.
[0017] A further technical solution is that the defoamer in the first auxiliary agent is selected from ShinEtsu KS-603, the leveling agent is selected from BYK-310, and the dispersant is selected from BYK Disperbyk-2150.
[0018] A further technical solution is that the defoamer in the second auxiliary agent is selected from BYK019, the leveling agent is selected from BASF-EFKA3600, and the dispersant is selected from TIGO-Dispers 655.
[0019] A further technical solution is that the mass ratio of the component A to the component B is 1:0.9-1.1, and the preferred mass ratio is 1:1. The component A and the component B are prepared and stored separately, and then mixed for use.
[0020] In a second aspect, the present invention also provides a method for preparing the epoxy adhesive for semiconductor cutting splicing rods according to the first aspect, comprising the following steps: POSS-epoxy caged polysilsesquioxane, phenolic epoxy, a first filler and a first auxiliary agent are mixed and dispersed to prepare component A; POSS-mercapto caged polysilsesquioxane, modified amine curing agent, accelerator, second filler and second auxiliary agent are mixed and dispersed to prepare component B; Mix component A and component B in proportion and use immediately.
[0021] Compared with the prior art, the technical effects achieved by the present invention include: The epoxy glue for semiconductor cutting splicing rods provided by the present invention has a synergistic effect between the components under the compounding of component A (mainly comprising POSS-epoxy, phenolic epoxy) and component B (mainly comprising POSS-thiol curing agent, modified amine curing agent), and the obtained colloid is similar to the structure of semiconductor silicon wafer or silicon carbide after curing, and the hardness and strength are close to the hardness, strength and crystal characteristics of semiconductor materials, which helps to improve the compatibility of epoxy glue with semiconductor materials; the POSS structure is an inorganic core composed of a silicon oxygen skeleton alternately connected by Si-O, which is similar to the skeleton of semiconductor silicon wafer or silicon carbide, supplemented by phenolic epoxy and modified amine curing agent, has good curing speed, viscosity and low water absorption, and adopts fillers with low linear expansion coefficient, which can better fill the bonding interface and reduce volume change. And the epoxy glue of the present invention has a higher glass transition temperature after curing, can tolerate temperature changes in the cutting process, hardness is less affected by temperature, and remains almost unchanged, so that semiconductor materials can pass through tungsten steel wire more smoothly, reduce wire bow, and improve cutting yield. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0024] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.
[0025] The embodiment of the present invention provides an epoxy adhesive for semiconductor cutting and splicing rods, comprising component A and component B; The component A comprises the following ingredients in parts by weight: POSS-epoxy caged polysilsesquioxane 17-25 parts by weight; 8-15 parts by weight of phenolic epoxy; 58-72 parts by weight of the first filler; 2-5 parts by weight of the first auxiliary agent; The B component includes the following ingredients in parts by weight: POSS-mercapto caged polysilsesquioxane 17-23 parts by weight; 5-10 parts by weight of modified amine curing agent; 3-5 parts by weight of accelerator; 60-70 parts by weight of the second filler; The second auxiliary agent is 2-3 parts by weight.
[0026] The following is an introduction to each ingredient: The POSS-epoxy caged polysilsesquioxane of the present invention comprises at least one of octa-glycidyl ether POSS-glycidyl ether oxypropyl caged polysilsesquioxane (such as structural formula 1), alicyclic epoxy POSS-octa-epoxycyclohexylethyl caged polysilsesquioxane (such as structural formula 2), and glycidyl ether oxypropyl cyclotetrasiloxane.
[0027] Structural formula 1, Structural formula 2, R=CH2CH2CH2OCH2(CHCH2O).
[0028] The POSS-epoxy caged polysilsesquioxane used in the embodiment of the present invention is octa-glycidyl ether POSS-glycidyl ether oxypropyl caged polysilsesquioxane.
[0029] The phenolic epoxy of the present invention comprises at least one of EPICLON HP-4710 (super high heat resistant epoxy resin, such as structural formula 3), phenolic epoxy with DCPD structure (diethylcyclopentadiene phenolic epoxy, such as structural formula 4), and NPPN-638 phenolic epoxy.
[0030] Structural formula 3, Structural formula 4, R = glycidyl ether, n = 1-2.
[0031] The phenolic epoxy used in the embodiment of the present invention is a combination of EPICLON HP-4710 and diethylcyclopentadiene phenolic epoxy DCPD, and the usage ratio of the two is 1:2.
[0032] The first filler used in the embodiment of the present invention is a combination of spherical silica, spherical alumina, and spherical silicon carbide with a low linear expansion coefficient, and the usage ratio of the three is 2:3:5. Among them, the spherical silica is a combination of 5μm spherical silica, 0.5μm spherical silica, and 0.05μm spherical silica in a ratio of 10:2:1; the spherical alumina is a combination of 3μm spherical alumina, 0.5μm spherical alumina, and 0.03μm spherical alumina in a ratio of 8:2:1; the spherical silicon carbide is a combination of 8μm spherical silicon carbide, 1μm spherical silicon carbide, and 0.05μm spherical silicon carbide in a ratio of 7:2:1.
[0033] The first auxiliary agent used in the embodiment of the present invention is a combination of defoamer ShinEtsu KS-603, leveling agent BYK-310, and dispersant Disperbyk-2150, wherein the ratio of defoamer: leveling agent: dispersant is 6:2:2.
[0034] The POSS-mercapto cage-like polysilsesquioxane used in the embodiment of the present invention is shown in structural formula 5: Structural formula 5, R = mercaptopropionate.
[0035] The modified amine curing agent used in the embodiment of the present invention is obtained by condensation reaction of 3,3-dimethyl-4,4-diaminodicyclohexylmethane (DMDC) and thiourea. The specific preparation process is as follows: 490 g of 3,3'-dimethyl-4,4-diaminodicyclohexylmethane was added to the reactor, the stirring motor was turned on, the temperature was raised and stirred until the temperature reached 95°C, and then 76 g of thiourea was added to the reactor, stirred and heated to 150°C under the protection of nitrogen atmosphere, and the reaction was observed to produce gas, and then heating was continued for 3 hours, the temperature was raised to 170°C, and the vacuum was turned on for 60 minutes, and then the temperature was lowered and the material was discharged to obtain a high Tg modified amine curing agent that can be cured quickly.
[0036] The accelerator used in the embodiment of the present invention is a combination of Versamine EH-50, 2.4.6-tri (N, N-dimethyl-4-amino-2-azabutyl) phenol (ACC 2950), and HI-54K, and the usage ratio of the three is EH-50: 2950: 54K = 2: 3: 5.
[0037] The composition of the second filler used in the embodiment of the present invention is the same as that of the first filler.
[0038] The second auxiliary agent used in the embodiment of the present invention is a combination of defoamer BYK019, leveling agent BASF-EFKA3600, and dispersant TIGO-Dispers 655. The ratio of defoamer: leveling agent: dispersant is 6:2:2.
[0039] The embodiment of the present invention also provides a method for preparing the above-mentioned epoxy adhesive for semiconductor cutting and splicing rods, comprising the following steps: Preparation of component A: POSS-epoxy caged polysilsesquioxane, phenolic epoxy, the first filler and the first auxiliary agent were put into a 2 L planetary power mixer according to the formula, the temperature was raised to 45 ° C within 30 min, vacuum was turned on and stirred for 2 h (speed 100 rmp / min, dispersion speed 800 rmp / min), and the material was discharged after cooling to room temperature, and sealed with nitrogen to obtain component A.
[0040] Preparation of component B: POSS-mercapto caged polysilsesquioxane, modified amine curing agent, accelerator, second filler and second auxiliary agent were put into a 2 L planetary power mixer according to the formula, heated to 45 °C within 30 min, vacuumed and stirred for 2 h (rotation speed 100 rmp / min, dispersion speed 800 rmp / min), discharged after cooling to room temperature, sealed and packaged with nitrogen, and component B was obtained.
[0041] The above-mentioned component A and component B are prepared and stored separately, and then mixed at a mass ratio of 1:1 before use, and are ready for use.
[0042] According to the ratios in Tables 1 and 2 below, the above method was used to prepare the component A and component B of each embodiment. Table 1 shows the composition and dosage of the component A of each embodiment, and Table 2 shows the composition and dosage of the component B of each embodiment.
[0043] Table 1 Composition and dosage of component A in each example
[0044] It should be noted that in Comparative Example A5, only POSS-epoxy was replaced by tetrafunctional glycidylamine (AG-80H), and the other components were the same as those in the embodiment; in Comparative Example A6, only phenolic epoxy was replaced by triglycidyl p-aminophenol (AFG-90), and the other components were the same as those in the embodiment.
[0045] Table 2 Composition and dosage of component B in each example
[0046] It should be noted that in Comparative Example B5, only the POSS-mercapto group was replaced by dipentaerythritol hexa(3-mercaptopropionic acid), and the other components were the same as those in the example; in Comparative Example B6, only the modified amine curing agent was Huntsman Capcure 3-800, and the other components were the same as those in the example.
[0047] The component A and the component B of the above-mentioned embodiments are combined in a mass ratio of 1:1 as shown in the following Table 3 to prepare epoxy adhesives for semiconductor cutting and splicing rods of different embodiments.
[0048] Table 3 Composition of epoxy adhesive for semiconductor cutting and splicing rods of Examples 1-8 composition Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Component A Example A1 Example A2 Example A3 Example A4 Comparative Example A5 Comparative Example A6 Comparative Example A5 Example A2 Component B Example B1 Example B2 Example B3 Example B4 Comparative Example B5 Comparative Example B6 Example B3 Comparative Example B6 The epoxy glue for semiconductor cutting splicing sticks (hereinafter referred to as "splicing stick glue") obtained in the above Examples 1-8 and two commercially available splicing stick glues were subjected to the following performance tests: Shore D hardness tester: Prepare the rubber sticks into round rubber blocks with a diameter of 6-8mm and a weight of 15-25g. Test the Shore D hardness of each round rubber block according to the national standard GB / T2411-2008. Test in an oven at 100℃. Quickly test the hardness of 5 points and take the average value.
[0049] Water absorption test: After the hardness test, the round rubber block is restored to room temperature, and then immersed in 25℃ water. After 24 hours, the weight change of the rubber block is tested. Five samples are taken from each group and the average value is taken. Low water absorption can ensure that the material can effectively prevent water vapor from entering the colloid during the cutting waiting process or the cutting process, thereby reducing the glass transition temperature of the colloid.
[0050] Glass transition temperature (Tg) test: Each rubber is tested using TMA according to GB / T 19466.2. The higher the Tg value, the higher the temperature at which the material changes from glass to rubber, indicating good temperature resistance.
[0051] Impact toughness (SM) test: Each rubber stick is tested using the standard method of GB / T 1843-2008. Impact toughness represents the mechanical strength of the material during the impact process, which can be characterized as the toughness of the material. The smaller the value, the greater the brittleness of the material.
[0052] Linear expansion coefficient (CTE): According to GB / T1036-2008 "Test method for linear expansion coefficient of new materials", the linear expansion coefficient of each glue stick is tested below Tg and above Tg. The lower linear expansion coefficient ensures that the colloid material will not generate large stress due to temperature changes during the cutting process, which will lead to the destruction of semiconductor materials.
[0053] Cutting yield test: Use the splicing glue provided in each embodiment and the commercially available splicing rod to splice the silicon carbide rods, and perform diamond wire cutting on the spliced silicon rods, with the number of cutting knives being 30. The tungsten diamond wire has a line speed of 25m / s, a wire diameter of 35μm, and a wire mesh spacing of 330μm. The poor cutting is summarized as silicon carbide sheet line marks and fragments, and the cutting yield is calculated. Yield = number of qualified pieces / total number of cut pieces.
[0054] Commercially available 1 is Prober / A-8860 stick glue, and commercially available 2 is SK / R-677 stick glue.
[0055] The test results of the above test items are shown in Table 4.
[0056] Table 4 Test results
[0057] According to the test results in Table 4, the glue sticks provided by the embodiments of the present invention (Examples 1-4), when compounded with component A and component B containing specific ingredients, the obtained solidified product shows good performance in terms of hardness, Tg, temperature resistance, etc., and can meet the requirements of semiconductor cutting: it has a water absorption rate of less than 0.3%, which can effectively prevent water vapor from entering during the cutting process; the Shore hardness is as high as 97HD, which is similar to the hardness of semiconductor materials, and the lower impact toughness indicates that the colloid is brittle after curing, which is close to the crystal properties of semiconductor materials; and the glass transition temperature is above 130°C, which can withstand the temperature of the cutting front end (50-100°C), and at the same time, the linear expansion coefficient at Tg and the linear expansion coefficient on Tg are much lower than those of Examples 5-8 and two commercially available glue sticks, and it has the advantage of good temperature resistance.
[0058] Compared with Examples 1-4, the stick glue of Example 5 uses a combination of tetrafunctional glycidylamine (AG-80H) and phenolic epoxy in component A, and a combination of hexa(3-mercaptopropionic acid) dipentaerythritol ester and a modified amine curing agent in component B, which does not contain a POSS skeleton structure, and its hardness, glass transition temperature, brittleness, etc. are far lower than those of Examples 1-4, and the linear expansion coefficient is high, showing the characteristics of poor temperature resistance; Compared with Examples 1-4, the stick glue of Example 6 uses a combination of POSS-epoxy and triglycidyl para-aminophenol (AFG-90) in component A, and a combination of POSS-thiol curing agent and Huntsman Capcure 3-800 in component B. Although it contains a POSS skeleton structure, the hardness, glass transition temperature, brittleness, etc. of the obtained cured product are far lower than those of Examples 1-4, and the linear expansion coefficient is high, showing the characteristics of poor temperature resistance. The results of Examples 5 and 6 show that the cured product obtained by using the non-component A and B components of the present invention cannot meet the actual processing requirements in terms of hardness, Tg, temperature resistance, etc.
[0059] Furthermore, in the stick glue of Example 7, component B is the same as Example B3 of the present invention, but component A adopts a combination of tetrafunctional glycidylamine (AG-80H) and phenolic epoxy, and the performance is slightly better than that of Example 5, indicating that component B of the present invention, with the combination of specific components, can improve the hardness, Tg, temperature resistance, etc. of the cured product; in the stick glue of Example 8, component A is the same as Example A2 of the present invention, but component B adopts a combination of POSS-thiol curing agent and Huntsman Capcure 3-800, and the performance is slightly better than that of Example 6, indicating that component A of the present invention, with the combination of specific components, can improve the hardness, Tg, temperature resistance, etc. of the cured product.
[0060] The above results illustrate that the epoxy glue for semiconductor cutting splicing rods provided by the present invention, under the compounding of component A (comprising POSS-epoxy, phenolic epoxy, a first filler, a first auxiliary agent) and component B (comprising POSS-thiol curing agent, modified amine curing agent, accelerator, second filler, and second auxiliary agent), has a synergistic effect between the components, so that the obtained splicing rod glue has a hardness and brittleness close to those of the semiconductor material after curing, has better compatibility with the semiconductor material, and has low water absorption and high glass transition temperature. The excellent temperature resistance can better adapt to the cutting and splicing of the third-generation semiconductor high-brittle materials, can ensure that the hardness after curing, especially the hardness during cutting, remains unchanged, the temperature change during the cutting process will not damage the semiconductor material, can pass the tungsten steel wire more smoothly, reduce the wire bow, and improve the cutting yield.
[0061] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0062] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. An epoxy adhesive for semiconductor cutting and splicing rods, characterized in that: It includes component A and component B; The component A comprises the following ingredients in parts by weight: POSS-epoxy caged polysilsesquioxane 17-25 parts by weight; 8-15 parts by weight of phenolic epoxy; 58-72 parts by weight of the first filler; 2-5 parts by weight of the first auxiliary agent; The B component includes the following ingredients in parts by weight: POSS-mercapto caged polysilsesquioxane 17-23 parts by weight; 5-10 parts by weight of modified amine curing agent; 3-5 parts by weight of accelerator; 60-70 parts by weight of the second filler; The second auxiliary agent is 2-3 parts by weight.
2. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The POSS-epoxy caged polysilsesquioxane includes at least one of octa-glycidyl ether POSS-glycidyl ether oxygen propyl caged polysilsesquioxane, alicyclic epoxy POSS-octa-epoxy cyclohexylethyl caged polysilsesquioxane, and glycidyl ether oxygen propyl cyclotetrasiloxane.
3. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The novolac epoxy comprises at least one of EPICLON HP-4710, a novolac epoxy having a DCPD structure, and NPPN-638 novolac epoxy.
4. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The general formula of the POSS-mercapto cage-like polysilsesquioxane is (RSiO 3 / 2 )n, R is mercaptopropionate, n=8.
5. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The modified amine curing agent is obtained by condensing 3,3-dimethyl-4,4-diaminodicyclohexylmethane and thiourea.
6. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The first filler and the second filler are independently selected from at least one of spherical silica, spherical alumina and spherical silicon carbide with low linear expansion coefficient.
7. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The accelerator includes at least one of Versamine EH-50, ACC 2950, and HI-54K.
8. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The first auxiliary agent and the second auxiliary agent independently include at least one of a defoamer, a leveling agent and a dispersant.
9. The epoxy adhesive for semiconductor cutting and splicing sticks according to claim 1, characterized in that: The mass ratio of the component A to the component B is 1:0.9-1.
1. The component A and the component B are prepared and stored separately, and then mixed for use.
10. A method for preparing the epoxy adhesive for semiconductor cutting and splicing sticks according to any one of claims 1 to 9, characterized in that: The following steps are involved: POSS-epoxy caged polysilsesquioxane, phenolic epoxy, a first filler and a first auxiliary agent are mixed and dispersed to prepare component A; POSS-mercapto caged polysilsesquioxane, modified amine curing agent, accelerator, second filler and second auxiliary agent are mixed and dispersed to prepare component B; Mix component A and component B in proportion and use immediately.
Citation Information
Patent Citations
Epoxy Resin Adhesives, Their Preparation Methods, and Applications
CN115651580B
Silicone rod joint glue and its preparation method and application
CN117247756B
Bi-component rod splicing glue as well as preparation method and application thereof
CN118064089A
Abrasion-resistant epoxy mortar with low thermal linear expansion coefficient and preparation method thereof
CN115010402A
Epoxy resin based on modified POSS (Polyhedral Oligomeric Silsesquioxane) interpenetrating network synergistic reinforcement and toughening and preparation method thereof
CN115785616A